Marketization of Shadow Education in Switzerland: How “Edupreneurs” Promote Preparation Programmes for a Selective School Transition - Sara Landolt; Itta Bauer (Education Sciences)
Private supplementary tutoring (PST) is a flourishing market for edupreneurs whose services relate closely to mainstream education. While international research elaborates on geographical variations in PST and edupreneurs’ marketing strategies, the PST market in Switzerland has been largely understudied. This paper contributes to fill this research gap by presenting a thematic analysis of the websites of edupreneurs offering preparation programmes for the highly selective central entrance examination (CEE) to the academically focused public school track of Gymnasium in Zurich. Conceptually, we draw on “problematization” and “commodificiation” as key terms elaborated by “geographies of marketization”. With this performative conceptualisation of the education market, we examine the marketing strategies of the edupreneurs offering CEE preparation courses. We offer two contributions to the existing research. First, the analysis elaborates that private CEE preparation courses are advertised as a market solution that compensates for an omission caused by public education. Second, we show how edupreneurs use rational and emotional arguments to convince families of the need of booking CEE preparation courses for their children. In the discussion, we engage with the findings of our local case study and argue that selective educational transitions have much wider relevance for policy and society elsewhere.